Biobehavioral mechanisms of topiramate's effects on alcohol use: an investigation pairing laboratory and ecological momentary assessments. (29th October 2014) - Miranda, Robert; MacKillop, James; Treloar, Hayley; Blanchard, Alexander; Tidey, Jennifer W.; Swift, Robert M.; Chun, Thomas; Rohsenow, Damaris J.; Monti, Peter M.
Abstract: Topiramate reduces drinking, but little is known about the mechanisms that precipitate this effect. This double‐blind randomized placebo‐controlled study assessed the putative mechanisms by which topiramate reduces alcohol use among 96 adult non‐treatment‐seeking heavy drinkers in a laboratory‐based alcohol cue reactivity assessment and in the natural environment using ecological momentary assessment methods. Topiramate reduced the quantity of alcohol heavy drinkers consumed on drinking days and reduced craving while participants were drinking but did not affect craving outside of drinking episodes in either the laboratory or in the natural environment. Topiramate did not alter the stimulant or sedative effects of alcohol ingestion during the ascending limb of the blood alcohol curve. A direct test of putative mechanisms of action using multilevel structural equation mediation models showed that topiramate reduced drinking indirectly by blunting alcohol‐induced craving. These findings provide the first real‐time prospective evidence that topiramate reduces drinking by reducing alcohol's priming effects on craving and highlight the importance of craving as an important treatment target of pharmacotherapy for alcoholism.